2019
DOI: 10.3390/su11030660
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Approaches for Urban Functional Zones Classification Based on Multi-Source Geospatial Data: A Case Study in Yuzhong District, Chongqing, China

Abstract: Accurate and timely classification and monitoring of urban functional zones prove to be significant in rapidly developing cities, to better understand the real and varying urban functions of cities to support urban planning and management. Many efforts have been undertaken to identify urban functional zones using various classification approaches and multi-source geospatial datasets. The complexity of this category of classification poses tremendous challenges to these studies especially in terms of classifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…It could be said that some XGBoost parameters have a significant effect on the output model, including col-sample_bytree, subsample, max_depth and nrounds [13].…”
Section: Application Of Extreme Gradient Boosting (Xgboost) Model For Landslide Susceptibility Mappingmentioning
confidence: 99%
“…It could be said that some XGBoost parameters have a significant effect on the output model, including col-sample_bytree, subsample, max_depth and nrounds [13].…”
Section: Application Of Extreme Gradient Boosting (Xgboost) Model For Landslide Susceptibility Mappingmentioning
confidence: 99%
“…The total area of Guangzhou Economic and Technological Development Zone is about 33.35 km 2 , with its GDP (Gross Domestic Product) reaching 320.953 billion yuan in 2017. The specific location and scope of the study area are shown in Figure 1 POI data [40,41]. However, these methods also have some problems.…”
Section: Study Areamentioning
confidence: 99%
“…They proposed a framework named DRoF that discovers regions with different functions to identify Beijing's functional areas [39]. Previous studies illustrate that we can identify and zone the urban and rural borders, logistics patterns, or urban functional areas by using POI data [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…The acquisition of these socio-economic data includes web crawlers, open API interfaces, and purchases from service providers. Since possible privacy issues limit wide applicability, the above are seldom used as the single data source [40,41]. The identification of urban functional zones based on multi-source data increases the semantic information, improves the spatial and temporal resolution, and provides more accurate results for urban functional zone identification [29,40,42].…”
Section: Data Sources Of Urban Functional Zone Researchmentioning
confidence: 99%